Lapsiines and hisponines as phylogenetically basal salticid spiders (Araneae: Salticidae) - Maddison, Wayne P.; Needham, Karen M. (Zootaxa, 2006)
Increased phylogenetic resolution of the basal lineages of salticid spiders will help us understand their early evolution and provide better outgroups for phylogenetic studies within the major clades. We gathered sequences of nuclear and mitochondrial gene regions (28S, 18S, Histone 3, 16S-ND1, CO1) and used them to reconstruct salticid phylogeny by parsimony, likelihood and Bayesian methods. Our results confirm that lapsiines and hisponines are among the basal salticids, i.e. outside the major clade Salticoida. The lapsiines are resolved as sister group to the spartaeines. The precise placement of hisponines is unclear, but they may represent a deep-branching lineage independent from the spartaeines.